Impact of APE1/Ref-1 Redox Inhibition on Pancreatic Tumor Growth - Fishel, Melissa L. (2011)
Pancreatic cancer is an especially deadly form of cancer with a survival rate <2%. Pancreatic cancers respond poorly to existing chemotherapeutic agents and radiation, and progress for the treatment of pancreatic cancer remains elusive. To address this unmet medical need, a better understanding of critical pathways and molecular mechanisms involved in pancreatic tumor development, progression and resistance to traditional therapy is therefore critical. Reduction-oxidation (redox) signaling systems are emerging as important targets in pancreatic cancer. AP endonuclease1/ Redox effector factor 1 (APE1/Ref-1) is upregulated in human pancreatic cancer cells and modulation of its redox activity blocks the proliferation and migration of pancreatic cancer cells as well as pancreatic cancer-associated endothelial cells (PCECs) in vitro. Modulation of APE1/Ref-1 using a specific inhibitor of APE1/Ref-1’s redox function, E3330 leads to a decrease in transcription factor activity for NFκB, AP-1, and HIF1 in vitro. This study aims to further establish the redox signaling protein APE1/Ref-1 as a molecular target in pancreatic cancer. Here, we show that inhibition of APE1/Ref-1 via E3330 results in tumor growth inhibition in cell lines as well as pancreatic cancer xenograft models in mice. Pharmacokinetic (PK) studies also demonstrate that E3330 attains >10 μM blood concentrations and is detectable in tumor xenografts. Through inhibition of APE1/Ref-1, the activity of NFκB, AP-1, and HIF1α which are key transcriptional regulators involved in survival, invasion and metastasis is blocked. These data indicate that E3330, inhibitor of APE1/Ref-1, has potential in pancreatic cancer and clinical investigation of APE1/Ref-1 molecular target is warranted.